Takayasu’s Arteritis Presenting as Ischemic Stroke in Young Patient - Sehrish Iqbal, Sehrish Iqbal; Awais Abbasi, Awais Abbasi; Noor Fatima, Noor Fatima; Muhammad Hamza, Muhammad Hamza; Najia Mahmood, Najia Mahmood; Muhammad Khurram, Muhammad Khurram (Students' Supplement of Journal of Rawalpindi Medical College, 2022)
Takayasu’s arteritis is a chronic inflammatory vasculopathy. It commonly affects large blood vessels like aorta and its branches. Disease prevalence is more in women in second to third decade of life. Higher frequency of diseases has been noted in in Japan, Southeast Asia, India and Mexico. Takayasu’s arteritis can present with various neurological complications. Stoke is prominent of these, it is noted in 10% of patients.1 stroke in Takayasu’s arteritis are mainly due to fibrosis and thickening of arterial walls. Takayasu arteritis having initial manifestation of stroke is uncommon.2 Here we present a case of stroke in young female in whom diagnosis of Takayasu’s arteritis was considered.